Material Characterization Of Hybrid Composite: Experimental Using Strain GAUGE/DIC With Finite Element Modelling Macro/Micro Scalens - Ab Ghani, Ahmad Fuad; Mahmud , Jamaluddin (Trans tech Publication, Switzerland, 2017)
-